Tourism management in warm-water island destinations - McLeod, Michelle Theresa; Croes, Robertico (CABI series in tourism management research, 2018)
"Warm-water island destinations face unprecedented adjustment challenges in the wake of the increasing process of globalization, and are in search of appropriate policy responses. It is critical for these islands to understand how these challenges affect tourism performance and impact their residents. This book provides a platform for emerging systemic perspectives of the various aspects of island tourism concerning these global challenges with the view that strategies for the management and development of tourism in island environments can be improved. Several chapters focus on Cuba and the potential impacts of its reinsertion in the tourism landscape of the Western Hemisphere" ...